Solubilized pancreatic extracellular matrix from juvenile pigs protects isolated human islets from hypoxia-induced damage: a viable option for clinical islet transplantation - Brandhorst, H; Krishtul, S; Brandhorst, D; Baruch, L; Machluf, M; Johnson, PRV (Hindawi Publishing Corporation, 2023)
The pancreatic extracellular matrix (ECM) is an enormously complex construct. Previous studies underline the challenges to identify the optimal combinations and ratios of individual ECM proteins for promoting survival and function of isolated and transplanted islets. This study aimed on assessing the efficiency of solubilized natural ECM extracted from juvenile pigs, an unlimited donor source. Isolated human islets were cultured under a hypoxic atmosphere (2% oxygen) in media supplemented with either solubilized porcine pancreatic ECM (ppECM) or a mixture of human ECM proteins composed of collagen-IV, laminin-521, and nidogen-1 (hEPM). Control islets were cultured under identical conditions without ECM-compounds. Reactive oxygen species production increased three-fold in controls but was reduced by hEPM or ppECM. Early apoptosis remained on preculture levels when islets were treated with hEPM or ppECM. Preculture viability was preserved when hEPM or ppECM was administered. Whilst controls failed to respond to glucose challenge, treatment with hEPM or ppECM preserved the physiological insulin response. In summary, overall survival was significantly highest in ppECM-treated islets. This study presents a new approach to protect human islets from hypoxia-induced damage by supplementing media with ppECM extracted from an unlimited donor source. The findings may also serve as starting point for a novel encapsulation technique to protect isolated human islets.